Relationship between grit and academic failure tolerance among nursing students: The mediating effect of psychological safety - Chung Hee Woo; Hyeoeun Lee (The Journal of Korean Academic Society of Nursing Education, 2026)
Purpose: The aim of this study was to examine the mediating effect of psychological safety on the relationship between grit and academic-failure tolerance among nursing students.Methods: Data were collected from 168 nursing students recruited through online communities between October 13 and 27, 2025, using convenience sampling. The data were analyzed using independent t-test, one-way ANOVA, Pearson’s correlation coefficients, and hierarchical regression analysis with IBM SPSS version 25.0. The mediating effect was further verified using bootstrapping via the SPSS PROCESS macro model 4.Results: Academic-failure tolerance was positively correlated with grit (r=.38, p